2004
DOI: 10.1136/jmg.2004.020669
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screening of the BARD1 gene: evidence for involvement of the Cys557Ser allele in hereditary susceptibility to breast cancer

Abstract: A pproximately 5-10% of all breast and ovarian cancers are thought to arise from a hereditary predisposition to the disease, 1 BRCA1 and BRCA2 being the most important susceptibility genes.2 3 Genomic alterations in BRCA1 are found in 40-50% of families with a high incidence of breast cancer (six or more cases), and in a majority (75-80%) of the families that display both breast and ovarian cancers.4 5 However, a significant portion of genetic aberrations predisposing to these cancers, especially in relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 41 publications
2
78
1
Order By: Relevance
“…None of the other variants identified here (that is, c.609A4C, c.1053G4C, c.1075del21 and c.1518C4T) was previously associated with an increased risk of breast cancer, 38,41 despite our results suggesting an association of the c.1518C4T (His506His) with an increased risk of breast cancer (P¼0.013), which is however not significant following Bonferroni correction. This finding would nonetheless have to be confirmed in much bigger cohorts.…”
Section: Brca1-interacting Gene Variants In Boc Families F Guénard Et Alcontrasting
confidence: 95%
See 1 more Smart Citation
“…None of the other variants identified here (that is, c.609A4C, c.1053G4C, c.1075del21 and c.1518C4T) was previously associated with an increased risk of breast cancer, 38,41 despite our results suggesting an association of the c.1518C4T (His506His) with an increased risk of breast cancer (P¼0.013), which is however not significant following Bonferroni correction. This finding would nonetheless have to be confirmed in much bigger cohorts.…”
Section: Brca1-interacting Gene Variants In Boc Families F Guénard Et Alcontrasting
confidence: 95%
“…34 The interaction of BRCA1 with RNA pol II 11 and DHX9 35 suggested a role for BARD1 in TCR. The BARD1 gene has been reported to be targeted by somatic 36 and germline [37][38][39] mutations in breast and in ovarian 36,40 cancer cohorts. BARD1 mutations have been identified in hereditary breast/ovarian cancers from BRCA1/2-negative patients 37,41 and it was suggested that the Cys557Ser variant may represent a low-penetrance breast cancer susceptibility allele.…”
Section: Introductionmentioning
confidence: 99%
“…Mutation reports about BARD1 mention mostly missense mutations, a few silent mutations and one in-frame deletion [Thai et al, 1998;Ghimenti et al, 2002;Ishitobi et al, 2003;Karppinen et al, 2004;Sauer and Andrulis, 2005;Vahteristo et al, 2006;Huo et al, 2007;Gorringe et al, 2008], but obvious deleterious BARD1 germline mutations (e.g. protein truncating mutations) have not been found till now.…”
Section: Discussionmentioning
confidence: 99%
“…The p.Arg658Cys variant has been reported by three other groups. Thai and collaborators [1998] showed its presence in 1% of the Caucasian population, while Karppinen et al [2004] and Vahteristo et al [2006] reported this variant in respectively 3.2% and 1.9% of their Finnish familial cases but with equal frequencies observed in their controls. A possible explanation for this discrepancy could be a biased selection of our control samples.…”
Section: Discussionmentioning
confidence: 99%
“…Cys557Ser was suggested to increase familial breast cancer risk by fourfold, 13 and the Val507Met was associated with a two-fold elevation in postmenopausal breast cancer risk. 14 We evaluated these variants in extensive series of unselected and familial breast cancer patients, and healthy controls.…”
Section: Introductionmentioning
confidence: 99%